2021
DOI: 10.1007/s13178-021-00592-9
|View full text |Cite
|
Sign up to set email alerts
|

You, Me, and Them: Understanding Employees’ Use of Trans-Affirming Language within the Workplace

Abstract: Introduction As the benefits of workplace inclusion become progressively recognized, employers are making greater efforts to cultivate inclusive organizational environments where employees from diverse backgrounds can thrive. Yet academic research has often neglected issues of sexual orientation and gender diversity. We contribute to redressing this knowledge gap by examining processes of workplace inclusion for employees with diverse genders and sexualities, focusing on an under-researched area—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In 2020, the sample included 2606 (9.7%) cisgender non‐heterosexual men 2238 (8.4%) cisgender non‐heterosexual women, 90 (0.3%) trans men, 114 (0.4%) trans woman, 73 (0.3%) trans non‐binary (assigned male at birth), 139 (0.5%) trans non‐binary (assigned female at birth) (Perales et al 2021a)…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the sample included 2606 (9.7%) cisgender non‐heterosexual men 2238 (8.4%) cisgender non‐heterosexual women, 90 (0.3%) trans men, 114 (0.4%) trans woman, 73 (0.3%) trans non‐binary (assigned male at birth), 139 (0.5%) trans non‐binary (assigned female at birth) (Perales et al 2021a)…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have focused on identity support and disclosure, or the use of language and gender-affirming behaviours (Huffman et al, 2021;Perales, 2022;Perales, Ablaza, Tomaszewski, et al, 2022). Working environments for trans and gender-diverse individuals can be particularly challenging, especially for people undergoing a transition in the workplace, who may exhibit distress, anxiety, and depression (Brewster et al, 2012).…”
Section: Workplace Experiences Of Lgbtq+ People: Existing Empirical E...mentioning
confidence: 99%
“…As is the case in educational settings, policies and practices within workplaces have been identified that result in better outcomes for LGBTQA + people. These include, for example, workplace diversity training and workplace employee networks or ally networks [ 19 ]. LGBTQ people within workplaces that have inclusive policies and practices in place, are more likely to feel that their workplace is affirming or safe [ 19 , 20 ] and to feel safe to disclose their identity [ 20 , 21 ], as well as experiencing greater equality and better career prospects within the workplace [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These include, for example, workplace diversity training and workplace employee networks or ally networks [ 19 ]. LGBTQ people within workplaces that have inclusive policies and practices in place, are more likely to feel that their workplace is affirming or safe [ 19 , 20 ] and to feel safe to disclose their identity [ 20 , 21 ], as well as experiencing greater equality and better career prospects within the workplace [ 22 ]. However, little research has explored the mental health or wellbeing implications of affirming workplaces for LGBTQA + people, and none to our knowledge with a focus on LGBTQA + youth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation